c-Almost periodic type functions and applications - M. T. Khalladi, M. Kostic, M. Pinto, A. Rahmani, D. Velinov (De Gruyter, 2020)
In this paper, we introduce several various classes of c-almost periodic type functions and their Stepanov generalizations, where c 2 C and |c| = 1. We also consider the corresponding classes of c-almost periodic type functions depending on two variables and prove several related composition principles. Plenty of illustrative examples and applications are presented.
Keywords: c-almost periodic functions, c-uniformly recurrent functions, semi-c-periodic functions, convolution products, abstract fractional semilinear inclusions